Activation of Adrenal Steroidogenesis and an Improvement of Mood Balance in Postmenopausal Females after Spa Treatment Based on Physical Activity - Honců, Pavla; Hill, Martin; Bičíková, Marie; Jandová, Dobroslava; Velíková, Marta; Kajzar, Jiří; Kolátorová, Lucie; Bešťák, Jiří; Máčová, Ludmila; Kancheva, Radmila; Krejčí, Milada; Novotný, Jaroslav; et al. (International journal of molecular sciences, 2019)
Spa treatment can effectively reestablish mood balance in patients with psychiatric disorders. In light of the adrenal gland's role as a crossroad of psychosomatic medicine, this study evaluated changes in 88 circulating steroids and their relationships with a consolidation of somatic, psychosomatic and psychiatric components from a modified N-5 neurotic questionnaire in 46 postmenopausal 50+ women with anxiety-depressive complaints. The patients underwent a standardized one-month intervention therapy with physical activity and an optimized daily regimen in a spa in the Czech Republic. All participants were on medication with selective serotonin reuptake inhibitors. An increase of adrenal steroidogenesis after intervention indicated a reinstatement of the hypothalamic-pituitary-adrenal axis. The increases of many of these steroids were likely beneficial to patients, including immunoprotective adrenal androgens and their metabolites, neuroactive steroids that stimulate mental activity but protect from excitotoxicity, steroids that suppress pain perception and fear, steroids that consolidate insulin secretion, and steroids that improve xenobiotic clearance. The positive associations between the initial values of neurotic symptoms and their declines after the intervention, as well as between initial adrenal activity and the decline of neurotic symptoms, indicate that neurotic impairment may be alleviated by such therapy provided that the initial adrenal activity is not seriously disrupted.
Keywords: psychoterapie; mood balance; Steroids; afekt; Psychotherapy; určení symptomu; postmenopauza; Projective Techniques; steroid metabolome; adrenal; Aged; senioři; Exercise; Postmenopause; Affect; lidé; projektivní techniky; ženské pohlaví; Adrenal Glands; Humans; spa treatment; Symptom Assessment; nadledviny; steroidy; Female; postmenopausal females; cvičení; lidé středního věku; Middle Aged